Using Functional Near-Infrared Spectroscopy to Assess Brain Activation Evoked by Guilt and Shame - Duan, Lian; Feng, Qiudi; Xu, Pengfei (Frontiers in Human Neuroscience, 2020)
Functional near-infrared spectroscopy (fNIRS) is a promising brain imaging modality for studying the neural substrates of moral emotions. However, the feasibility of using fNIRS to measure moral emotions has not been established. In the present study, we used fNIRS to detect the brain activation evoked by two typical moral emotions — guilt and shame. We presented the participants with guilt and shame context to evoke emotional responses and measured the brain activity by using fNIRS. The univariate general linear model analysis showed significant activations for both emotions in the orbitofrontal cortex, dorsolateral prefrontal cortex (dlPFC) and middle temporal gyrus, and specific activation for guilt in the right temporo-parietal junction. The multivariate classification analysis showed an overall recognition accuracy of 52.50% which was significantly higher than the chance level in classifying the guilt, shame and neutral emotions. These results suggested the feasibility of using fNIRS to assess the brain activation evoked by guilt and shame, and demonstrated the potentials of fNIRS in studying the neural correlates of moral emotions.